Literatura polska w chorwackich przekładach od 1990 r. do 2007 r. / Polish Literature in Croatian Translation (1990—2007) - Čilić Škeljo, Đurđica; Vidović, Ivana (Przekłady Literatur Słowiańskich, 2009)
The paper deals with translations of Polish literary works into Croatian language in the period between 1990 and 2007. We took into consideration only those translations that were published as books or those published in Croatian journals as a part of a larger thematic piece dedicated to Polish literature. Apart from translations of literary works, the article deals with the translations of literary-historical and literary-theoretical studies, as well as linguistic works. Our detailed revision confirms high productivity of Croatian translators of Polish literature.